Test Potential of Selected Biological Control Fungi Against Phyllosticta zingiberi Under Laboratory Conditions - Martha Adiwaty Sihaloho; Hapsoh; Hasanuddin (Agroprimatech, 2025)
Leaf spot disease is one of the major constraints in red ginger (Zingiber officinale Rosch) cultivation, causing necrosis on leaves that reduces photosynthetic capacity and rhizome productivity. This study evaluated the antagonistic activity of four biological control agents Trichoderma koningii, Trichoderma harzianum, Gliocladium spp., and Gliocladium virens, against Phyllosticta zingiberi under in vitro conditions. The experiment was conducted at the Plant Pathology Laboratory, Faculty of Agriculture, University of Sumatera Utara, Medan, from January to March 2010. A Completely Randomized Design (CRD) with five treatments and five replications was used. The results showed that the highest growth inhibition was observed in Gliocladium spp. (46.23%) and T. harzianum (46.15%), followed by T. koningii (41.38%) and G. virens (27.24%). The control exhibited the lowest inhibition (6.43%). The observed suppression is attributed to mechanisms including mycoparasitism, production of antifungal metabolites, and competition for space and nutrients. The findings indicate that Gliocladium spp. and T. harzianum are the most effective biological control agents for managing leaf spot disease in red ginger